The Case of Insertional Adductor Tendinopathy of an International-Level 3,000-m Steeplechase Runner - Thomas, Ewan; Giaccone, Marcello; Iovane, Angelo; Polizzi, Gaspare; Petrucci, Marco; Messina, Giuseppe; Palma, Antonio (Frontiers in Sports and Active Living, 2021)
Background Groin pain is a frequent condition among athletes. One of the causes of groin pain is tendinopathy, a frequently diagnosed medical condition, which can also occur in the adductor muscles. Despite the high prevalence of this medical condition among athletes, it is infrequent to observe tendinopathic groin pain in in steeplechase runners. The aim of this case study is to describe the case of an international level 3000m steeplechase runner, with groin pain, which was subsequently diagnosed with adductor insertional tendinopathy. Case presentation We present the case of an Italian 3000 metres steeplechase and long distance runner, Ala Zoghlami (180cm; 57 kg) with groin pain, diagnosed as insertional adductor tendinopathy. The runner after manifesting the painful symptomatology, underwent medical screening (Ultrasound and MRI). The radiological investigations highlighted adductor tendinopathy. After refraining from training, the runner underwent medical and physical therapy which, in the first phase did not improve the painful symptomatology. Further evaluation, after six months from the initial training cessation, highlighted a case of malocclusion. Such was treated from a dentistry perspective with the creation of a personalized dental bite. Results A multidisciplinary approach which included medical and physical therapy, osteopathy and dentistry, in adjunct with refraining from training was able to reduce the symptomatology and allow a correct return to run (after 9 month from the first painful manifestation) of the steeplechase runner. To date Ala Zoghlami, has fully recovered and was able to win the 3000 metres steeplechase race during the 2021 National Italian competition.